A specific pattern of phosphodiesterases controls the cAMP signals generated by different Gs-coupled receptors in adult rat ventricular myocytes - Rochais, Francesca (2006)
Compartmentation of cAMP is thought to generate the specificity of Gs-coupled receptor action in cardiac myocytes, with phosphodiesterases (PDEs) playing a major role in this process by preventing cAMP diffusion. We tested this hypothesis in adult rat ventricular myocytes by characterizing PDEs involved in the regulation of cAMP signals and L-type Ca2+ current (ICa,L) on stimulation with β1-adrenergic receptors (β1-ARs), β2-ARs, glucagon receptors (Glu-Rs) and prostaglandin E1 receptors (PGE1-Rs). All receptors but PGE1-R increased total cAMP, and inhibition of PDEs with 3-isobutyl-1-methylxanthine strongly potentiated these responses. When monitored in single cells by high-affinity cyclic nucleotide–gated (CNG) channels, stimulation of β1-AR and Glu-R increased cAMP, whereas β2-AR and PGE1-R had no detectable effect. Selective inhibition of PDE3 by cilostamide and PDE4 by Ro 20-1724 potentiated β1-AR cAMP signals, whereas Glu-R cAMP was augmented only by PD4 inhibition. PGE1-R and β2-AR generated substantial cAMP increases only when PDE3 and PDE4 were blocked. For all receptors except PGE1-R, the measurements of ICa,L closely matched the ones obtained with CNG channels. Indeed, PDE3 and PDE4 controlled β1-AR and β2-AR regulation of ICa,L, whereas only PDE4 controlled Glu-R regulation of ICa,L thus demonstrating that receptor–PDE coupling has functional implications downstream of cAMP. PGE1 had no effect on ICa,L even after blockade of PDE3 or PDE4, suggesting that other mechanisms prevent cAMP produced by PGE1 to diffuse to L-type Ca2+ channels. These results identify specific functional coupling of individual PDE families to Gs-coupled receptors as a major mechanism enabling cardiac cells to generate heterogeneous cAMP signals in response to different hormones.